Phytochemistry and Biological Activities of Guarea Genus (Meliaceae) - Wahyu Safriansyah; Siska Elisahbet Sinaga; Unang Supratman; Desi Harneti (Molecules, 2022)
Guarea is one of the largest genera of the American Meliaceae family, consisting of over 69 species which are widely distributed in Mexico, Argentina, and Africa and are used in traditional medicine for several diseases. Previous studies reported that the Guarea species produce secondary metabolites such as sesquiterpenoid, diterpenoid, triterpenoid, limonoid, steroid, and aromatic compounds. The preliminary chemical investigation commenced by isolating the limonoid compound, dihydrogedunin, in 1962; then, 240 compounds were obtained from the isolation and hydrodistillation process. Meanwhile, sesquiterpenoid is a significant compound with 52% of Guarea species. The extract and compounds were evaluated for their anti-inflammation, antimalarial, antiparasitic, antiprotozoal, antiviral, antimicrobial, insecticidal, antioxidant, phosphorylation inhibitor, and cytotoxic biological activities. The Guarea genus has also been reported as one of the sources of active compounds for medicinal chemistry. This review summarizes some descriptions regarding the types of Guarea species, especially ethnobotany and ethnopharmacology, such as the compounds isolated from the part of this genus, various isolation methods, and their bioactivities. The information can be used in further investigations to obtain more bioactive compounds and their reaction mechanisms.